Penyelesaian sengketa Perbankan Syariah di Luar Pengadilan Agama - Ratna Amalia, Cindy; Nurul Hidayah, Astika (LPPM Universitas Harapan Bangsa, 2024)
Law of the Republic of Indonesia Number 21 of 2008 concerning Sharia Banking still raises problems in the process of resolving cases within the scope of Sharia Banks. The scope of the Religious Courts and the General Courts have the same authority in resolving Islamic Banking disputes in Indonesia. This research was conducted to explore and analyze the absolute authority of judicial institutions in Indonesia in resolving cases related to Islamic banking in Indonesia. This research is normative juridical in nature by approaching the applicable laws and regulations associated with the legal issues studied. Based on the research, it is found that the District Court does not have absolute authority in resolving Islamic banking disputes. The settlement of Islamic Banking disputes according to Law Number 21 of 2008 concerning Islamic Banking can be done by choosing one of the paths, namely through litigation within the Religious Court, and secondly, non-litigation can be done by means of deliberation, mediation, the National Sharia Arbitration Board (BASYARNAS) or other authorized arbitration institutions, and the General Court. Keywords: authority, dispute resolution, islamic banking